Plan de formación de pastoral juvenil para las instituciones Educativas de la Casa Salesiana “Santo Domingo Savio” de Cayambe - Caiza Jami, Libia Celina (2015)
This research aimed to know the status of youth ministry in schools that the Salesian Community encourages in Cayambe and make a concrete proposal that strengthen and give significance . For this purpose an approach to ecclesial documents of Latin American Bishops and of the Salesian Congregation , which allowed conceptualize and define better the motivations and impacts of youth ministry was performed. Also information arose, through surveys , the actors of pastoral education community, young students , parents and colleagues , linked to the Salesians Education Centers (CES ) , about their satisfaction , needs and expectations Youth Ministry . However many pastoral interventions exist that are related to educational communities , these mostly suffer from planning, socialization , monitoring and evaluation , further , implementation is not always compatible with the pastoral guidelines , church or congregational and are not entirely integrated into the set of institutional planning.